Comorbidity in elderly patients with atrial fibrillation affects the “cost of illness” - S. V. Malchikova; N. S. Maksimchuk-Kolobova; M. V. Kazakovtseva (Фармакоэкономика, 2019)
Objective: to analyze whether comorbidity affects the cost of treatment and medical services in elderly patients with atrial fibrillation (AF). Materials and methods. We conducted a retrospective analysis of 98 patients with AF. Comorbidity was evaluated using the CIRS-G scale (Cumulative Illness Rating Scale for Geriatrics) and the Charlson criterion. The “cost of illness” calculations included direct costs only. Results. In elderly patients with AF (mean age 74.7±8.8 years), high rate of comorbidity was typically found. Charlson comorbidity index amounted to 4.0±1.8, and the CIRS-G score – to 8.0±2.8. AF is often associated with heart diseases such as hypertension – 98.9%, coronary heart disease – 27.6%, and congestive heart failure – 76.5%. A patient with AF received on average 7.5±3.8 medications. Direct costs amounted to 18298.2±9440.4 RUB per patient with AF per year. Of this amount, 78.8% were spent for outpatient treatment, 16.5% for hospitalization and 4.7% for ambulance service. Cardiac medications comprised 66.4% of the total direct costs. In patients with high comorbidity, there are high costs of treatment of concomitant diseases, high secondary costs as well as costs for a doctor visit. Conclusion. An average elderly patient with AF receives 7.5±3.8 permanent medications, which correlates with the severity of comorbidity by the Charlson index (r=0.59; p=0.000) and the CIRS-G score (r=0.29; p=0.004). Management of such patients at the outpatient clinic is by large (66.4%) associated with direct costs of the prescribed medications. However, patients with high comorbidity still need more vital drugs, as the cost of treatment of concomitant diseases increases. Notably, these patients spend 4 times more funds for drugs without proven efficacy.